Pengaruh Model Pembelajaran Discovery Learning Terhadap Hasil Belajar IPA di SMP Muhammadiyah 1 Kota Jambi: The Effect of Discovery Learning Learning Model on Science Learning Outcomes in Muhammadiyah 1 Junior High School in Jambi - Khairul Mustopa; Afreni Hamidah; Evita Anggereini (Universitas Jambi, 2020)
Vibration and wave material is one of the science materials that are considered difficult; the learning outcome of most students at SMP Muhammadiyah 1 Jambi City are still below the minimum requirement (65). This study aims to determine the differences in learning outcomes and implement discovery learning models on student learning outcomes in vibration and wave material. The research employed a pre-experimental design through pretest-posttest-control-design, carried out at SMP Muhammadiyah 1 Jambi City from February 17 to March 16, 2020. The sample selection was carried out using a simple random sampling technique. The average student learning outcomes in the control class's cognitive domain was 54,33, while the experimental class was 70,19. In the realm of attitudes, the average student learning outcomes in the control class was 73,58, while in the experimental class was 80. The independent-sample t-test for cognitive domain learning outcomes was 4,512 (> t table 2.063) and in the attitude domain was 2, 57 (> t table 2,063). Paired sample t score of learning outcomes in the cognitive domain was 1,259 (<t table 1,708), and in the realm of attitudes, was 0,0004 (<t table 1,708). It can be concluded that there are differences in student learning outcomes using discovery learning models, both in the cognitive and attitudinal domains.